2020
DOI: 10.1093/jee/toaa049
|View full text |Cite
|
Sign up to set email alerts
|

First Complete Genome of Lake Sinai Virus Lineage 3 and Genetic Diversity of Lake Sinai Virus Strains From Honey Bees and Bumble Bees

Abstract: The complete genome of Lake Sinai virus 3 (LSV3) was sequenced by the Ion Torrent next-generation sequencing (NGS) technology from an archive sample of honey bees collected in 2010. This strain M92/2010 is the first complete genome sequence of LSV lineage 3. From October 2016 to December 2017, 56 honey bee samples from 32 different locations and 41 bumble bee samples from five different locations were collected. These samples were tested using a specific reverse transcriptase-polymerase chain reaction (RT-PCR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(41 citation statements)
references
References 24 publications
2
39
0
Order By: Relevance
“…The result of testing by reaction (RT-PCR) method showed that and 75.92% of honeybee samples and 17.07% of bumblebee samples were LSV positive. The identified strains of LSV from bumblebees share from 98.6% to 99.4% nucleotide identity to the closest honeybee LSV strains collected from the same geographical area in Slovenia [5]. LSVs have also been also detected, with similar incidences and titres in historical European honeybee samples.…”
Section: Introductionmentioning
confidence: 73%
See 3 more Smart Citations
“…The result of testing by reaction (RT-PCR) method showed that and 75.92% of honeybee samples and 17.07% of bumblebee samples were LSV positive. The identified strains of LSV from bumblebees share from 98.6% to 99.4% nucleotide identity to the closest honeybee LSV strains collected from the same geographical area in Slovenia [5]. LSVs have also been also detected, with similar incidences and titres in historical European honeybee samples.…”
Section: Introductionmentioning
confidence: 73%
“…Nucleic acids of five honeybee viruses (ABPV, BQCV, CBPV, DWV and SBV) were detected using a specific method of reverse transcription and polymerase chain reaction (RT-PCR), as previously described [6]. The LSV was detected with a specific RT-PCR method [5] using previously described primers LSV 1765-F and LSV 2368-R [19]. Results were evaluated based on the size of RT-PCR products in the agarose gel as positive in the case of the expected product size: for ABPV 452 nucleotides (nt), for BQCV 770 nt, for CBPV 570 nt, for DWV 504 nt, for SBV 814 nt and for LSV 603 nt.…”
Section: The Prevalence Of Abpv Bqcv Cbpv Dwv Sbv and Lsv In Bummentioning
confidence: 99%
See 2 more Smart Citations
“…LSV replicates in honeybees that often harbour high viral burdens (10 8 –10 9 viral copies/bee) [ 5 ]. Although there are no obvious clinical symptoms attributed to LSV-positive honeybee families, their abundance and association with colonies of poor health are indications that different genetic strains of LSV might have a negative impact on honeybee health [ 28 ].…”
Section: Introductionmentioning
confidence: 99%